Integrated transcriptome and metabolome analysis of salinity tolerance in response to foliar application of choline chloride in rice (Oryza sativa L.) - Huo, Jingxin; Yu, Minglong; Feng, Naijie; Zheng, Dianfeng; Zhang, Rui; Xue, Yingbin; Khan, Aaqil; Zhou, Hang; Mei, Wanqi; Du, Xiaole; Shen, Xuefeng; Zhao, Liming; et al. (Frontiers in Plant Science, 2024)
Introduction Salt stress is a major abiotic stress that affects crop growth and productivity. Choline Chloride (CC) has been shown to enhance salt tolerance in various crops, but the underlying molecular mechanisms in rice remain unclear. Methods To investigate the regulatory mechanism of CC-mediated salt tolerance in rice, we conducted morpho-physiological, metabolomic, and transcriptomic analyses on two rice varieties (WSY, salt-tolerant, and HHZ, salt-sensitive) treated with 500 mg·L-1 CC under 0.3% NaCl stress. Results Our results showed that foliar application of CC improved morpho-physiological parameters such as root traits, seedling height, seedling strength index, seedling fullness, leaf area, photosynthetic parameters, photosynthetic pigments, starch, and fructose content under salt stress, while decreasing soluble sugar, sucrose, and sucrose phosphate synthase levels. Transcriptomic analysis revealed that CC regulation combined with salt treatment induced changes in the expression of genes related to starch and sucrose metabolism, the citric acid cycle, carbon sequestration in photosynthetic organs, carbon metabolism, and photosynthetic antenna proteins in both rice varieties. Metabolomic analysis further supported these findings, indicating that photosynthesis, carbon metabolism, and carbon fixation pathways were crucial in CC-mediated salt tolerance. Discussion The combined transcriptomic and metabolomic data suggest that CC treatment enhances rice salt tolerance by activating distinct transcriptional cascades and phytohormone signaling, along with multiple antioxidants and unique metabolic pathways. These findings provide a basis for further understanding the mechanisms of metabolite synthesis and gene regulation induced by CC in rice in response to salt stress, and may inform strategies for improving crop resilience to salt stress.